Control of lipid metabolism in chondrocytes is critical for skeletal growth - Aijaz Ahmad John; Yeon-Suk Yang; Jun Xie; Sachin Chaugule; Xu Xu; Ann-Hwee Lee; Kyoung-Mi Lee; Kwang Hwan Park; Guangping Gao; Jae-Hyuck Shim (Proceedings of the National Academy of Sciences, 2026)
Chondrodysplasia is a genetic disorder characterized by impaired cartilage development and bone growth. Dysregulation of the endoplasmic reticulum (ER) stress is associated with chondrodysplasia. Here, we demonstrate a critical role for the ER stress regulator PPP1R15B in chondrocyte development. PPP1R15B is a protein phosphatase that constitutively represses eIF2α phosphorylation to attenuate global protein translation in response to stress. Remarkably, deletion of Ppp1r15b in Prx1 + skeletal progenitors ( Ppp1r15b Prx1 ) impairs chondrogenesis, resulting in a disorganized growth plate, reduced trabecular bone, and shortened long bones in mice. Similarly, inducible deletion of Ppp1r15b in Col2 + chondroprogenitors ( Ppp1r15b Col2 ) leads to abnormal cartilage development and bone growth. Remarkably, no skeletal phenotype is observed in mice lacking Ppp1r15b in committed Osx + osteoprogenitors ( Ppp1r15b Osx ) and Dmp1 + mature osteoblasts and osteocytes ( Ppp1r15b Dmp1 ), indicating that its role is limited to regulation of chondrogenesis, not osteogenic differentiation. Mechanistically, PPP1R15B deletion increases eIF2α phosphorylation, which in turn enhances lipogenic gene expression by suppressing leptin expression. This effect was reversed in Ppp1r15b Prx1 mice by reconstitution with wild-type PPP1R15B, but not with a mutant form incapable of eIF2α dephosphorylation. Exogenous expression of leptin also reversed skeletal abnormalities in these mice. Collectively, these findings reveal a critical role for PPP1R15B in cartilage development through its regulation of lipid metabolism.